2020
DOI: 10.1016/j.ijfoodmicro.2020.108778
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome-microbiome signatures in the fermented beverage, Kombucha

Abstract: Metabolome-microbiome signatures in the fermented beverage, Kombucha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 52 publications
7
75
1
1
Order By: Relevance
“…The idea that biochemical properties of the environment contribute to spatial variability within a microbial community is not new [ 61 ]. In Lambic beer fermentations, Roos et al [ 62 ] found higher AAB counts correlated with higher metabolic activity (increased production of acetic acid, acetoin, and ethyl acetate) at the air/liquid interface.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that biochemical properties of the environment contribute to spatial variability within a microbial community is not new [ 61 ]. In Lambic beer fermentations, Roos et al [ 62 ] found higher AAB counts correlated with higher metabolic activity (increased production of acetic acid, acetoin, and ethyl acetate) at the air/liquid interface.…”
Section: Discussionmentioning
confidence: 99%
“…Shotgun metagenomics allows to overcome the challenges that affect both assembly based and mapping‐based metagenomic profiling (Laudadio et al ., 2019), particularly, of high‐complexity samples (Walsh et al ., 2016; Seol et al ., 2019; Sirén et al ., 2019), including KMC (Arıkan et al ., 2020; Villarreal‐Soto et al ., 2020). Hence, we have implemented a shotgun metagenomic approach to gather an unbiased snapshot of the community structure and potential functionality in KMC that were previously exposed to space and different levels of Mars‐like conditions, simulated on low Earth orbit outside the International Space Station (ISS), within the BIOMEX project (de Vera et al ., 2019; Podolich et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent metagenomics screening predicted the presence of opportunistic bacteria like Bacillus, Pseudomonas etc. [23,24], bacteriophages and even yeast viruses [25]. Yeast fraction changes in genera composition depending on geographical origin, and it consists of representatives of Zygosaccharomyces, Brettanomyces, Schizosaccharomyces, Saccharomyces, and Pichia [19].…”
Section: Kombucha Biological Structurementioning
confidence: 99%
“…Chemical analysis of kombucha revealed organic acids: acetic, gluconic, glucuronic, citric, L-lactic, malic, tartaric, malonic, oxalic, succinic, pyruvic, usnic; sugars: sucrose, glucose, fructose, and cellulose; vitamins B1, B2, B6, B12,K 2 and C; 14 amino acids; biogenic amines; purines; pigments; lipids; proteins; hydrolytic enzymes; ethanol; polyols; antibiotics; carbon dioxide; tea polyphenols; minerals Cu, Fe, Mn, Ni, and Zn; anions; insufficiently known products of yeast and bacterial metabolites; rutin and kombucha-specific theobromine [28][29][30].…”
Section: Kombucha Chemical Compositionmentioning
confidence: 99%